(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
Main Pateri is one of the Malay traditional medicinal practices that is still popular in the eastern part of Peninsular Malaysia, and is still one of the options selected by the local community to treat illnesses especially psychosomatic ones. This study was conducted to document the healing ritual of Main Pateri and to explore the physical environmental parameters during the ritual. In order to achieve this objective, a case study in Kampung Jedok, Ayer Lanas, Kelantan was chosen. Observation, in-depth interviews and measurements of physical environmental parameters including ambient temperature, relative humidity, wind velocity, light intensity and sound level were carried out. From the study, it can be concluded that the healing ritual of Main Pateri caused fluctuations in the physical environmental parameters due to the movement of the Tok Teri and the patient, as well as through the dance movements, musical instruments and the movement of audience. In addition, the natural environmental conditions also influenced the results of measurement. This study may serve as a fundamental basis for further and more detailed studies on the influence of Main Pateri and its relation to physical environmental parameters. However, such study would need to be performed in an enclosed and controlled environment. Keywords: Malay traditional medicine, Main Pateri, physical environment